Fabrication and Characterization of New Ti-TiO2-Al and Ti-TiO2--Pt Tunnel Diodes - Yaksh Rawal; Swaroop Ganguly; Maryam Shojaei Baghini (Active and Passive Electronic Components)
Remotely empowered wireless sensor networks use different energy resources including photovoltaic solar cells, wireless power transmission, and batteries. As another option the electromagnetic energy available in the ambient can be harvested to power these remote sensors. This is particularly valuable if it is desirable to harvest the ambient energy available in the wide range of electromagnetic spectrum. This has motivated the research for developing energy harvesting devices which can absorb this energy and produce a DC voltage. Rectenna, an antenna coupled with a rectifier, is the main component used for absorbing electromagnetic radiation at GHz and THz frequencies. Rectifying MIM tunnel diodes are able to operate at tens and hundreds of GHz frequency. As the preliminary steps towards development of high-frequency rectifiers, this paper presents fabrication and DC characterization of two new MIM diodes, Ti-TiO2-Al and Ti-TiO2-Pt. G-V analysis of the fabricated diodes verifies tunneling. Brinkman-Dynes-Rowell model is used to extract oxide thickness of which the derived value is around 9 nm. Ti-TiO2-Pt diode exhibits rectification ratio of 15 at 0.495 V, which is more than rectification ratio reported in earlier works.